A Study of the Solitary Wave Energy Attenuation through Pervious Concrete Breakwater - Sukcharoen, Teerathamrong; Kositgittiwong, Duangrudee; Ekkawatpanit, Chaiwat; Phakdeewiriyateerakul, Nophasit (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 27, 2022)
Coastal erosion is a primary problem for coastal communities worldwide. Furthermore, the climate change impact and the resulting sea-level rise have reduced the sediment transportation along the coast, deteriorated infrastructure, and the natural coastal environment. These significant concerns lead to extensive innovations in coastal protection. Breakwaters are coastal structures typically applied for shorelines protection and sheltering harbours by providing wave energy attenuation and reflecting amounts of wave currents. In the present study, pervious concrete is utilised as a permeable breakwater considering the influence of permeability introduced to deliver the ecological friendliness defence for shorelines. A physical experimental model evaluated four models of structures that differed in porosity (15%, 20%, 25% and 30%) to study and analyse the performance of pervious concrete breakwater over the solitary wave impact. Subsequently, the hydrodynamic scattering coefficient (i.e., reflection, transmission, and dissipation coefficient) is analysed by considering changes in physical parameters such as the relative water depth and the wave period. In addition, the physical properties (i.e., void ratio test and permeability test) were also investigated. The experiments were conducted in the open channel flume (12 m. long, 0.6 m. wide, and 0.8 m. high) at KMUTT. The results were analysed and indicate that the introduction of pervious concrete breakwater improves wave transmission, reflection, and wave dissipation performance. As a result, a pervious concrete breakwater is a feasible alternative for a prospective coastal protection structure.